Association between legal status, prenatal care utilization, severe perinatal and maternal morbidity. (13th November 2019) - Eslier, M; Schmitz, T; Luton, D; Mandelbrot, L; Estellat, C; Azria, E
Abstract: Background: Some groups of migrant women have a higher risk of inadequate prenatal care utilization (PCU), severe maternal morbidity (SMM) and severe perinatal morbidity (SPM). To better understand this association, our aim was to assess the association between the legal status and PCU, SMM and SPM during pregnancy. Methods: The analysis was performed in the database of the multicenter prospective PreCARE cohort. All pregnant women registered for delivery in 4 university hospital maternity units in Paris north area from October 2010 to May 2012 were included (N = 10 419). Women whose pregnancies ended before 22 weeks of gestation or who delivered in another maternity unit were excluded (N = 820). Women were distributed according to legal status in 4 groups: non-migrants, migrants with French or European nationality, legal migrants and undocumented migrants. The associations between the legal status and the composite variables of prenatal care utilization, SMM and SPM were tested through multivariate logistic regressions also adjusted for maternal characteristics. Results: The illegal status was associated with increased risk of inadequate prenatal care utilization [adjusted odds ratio (aOR) 2, 52 (2, 10 - 3, 01)]. Overall, the prevalence of SMM was 3, 2 % and SPM 7, 0 %. The illegal status was associated with higher risk of SMM [aOR 1, 84 (1, 21 - 2, 79)], especially severe hypertensive disorder of pregnancy [aOR 2, 29 (1, 19 - 4, 40)]. However, no significant association with SPM was found [aOR 1, 29 (0, 95 - 1, 74)]. The sensitivity analysis demonstrates that results do not change after exclusion of women who arrived less than 12 months before delivery and those who started their follow-up after 14 weeks of gestation. Conclusions: The illegal status was associated with an inadequate prenatal care utilization and a higher risk of SMM, especially severe hypertensive disorder of pregnancy. Key messages: The illegal status was associated with increased risk of inadequate prenatal care utilization. The illegal status was associated with higher risk of severe maternal morbidity during pregnancy.